Quelle place pour la Grande Guerre dans l’histoire contemporaine du Japon ? Quelques éléments de réflexion à partir d’un témoignage japonais - Frédéric Danesin (Les Cahiers de Framespa)
Considered as the main historical event in the beginning of the twentieth century, the Great War (1914-1918) is at the heart of a monumental and vivacious historiography. Though it is easy to notice how little attention is given to Japan’s role in this war, at least as little attention is granted to this war in Japanese modern history. Is it possible to write the history of Japan evading the years from 1905 to 1931? What was the Great War for Japan? This is quite a large question, but perhaps it is possible to get some humble elements of an answer through the thinking and work of Mizuno Hironori (水野広徳, 1875-1945).Being a soldier and a military columnist, a successful writer (as revealed by his book about the Russian-Japanese War (Kono Issen, 此の一戦)), and famous for his pacifist thinking in Imperialist Japan, it was during the period that he was being impressed by the devastation of the war during his stay in Europe in 1919 that he strengthen his convictions. Mizuno Hironori is as valuable an observer and intellectual as he is a witness (and sometimes actor) of the wars that involved Japan from 1904 to 1945.The evolution and thinking of Mizuno Hironori allows us to not only bring a Japanese testimony – a particular yet lacking perspective on the Great War – to determine the weight of the event for his contemporaries, but also to situate Japan in a historical continuity from 1905 to World War Two.